Properties of concrete containing shredded waste paper as an additive - B. A., Solahuddin; F. M., Yahaya (Elsevier Ltd, 2022)
Cement, sand, coarse aggregate and water are the materials used to make a concrete mixture. The abundance of waste paper was dumped in landfills and every year, the number of waste paper dumped is increasing. This situation causes great stress to the landfills as more spaces are needed. As more spaces or areas are needed, this might cause a loss of natural resources. The waste paper industry every year is increasing gradually. More spaces are needed for landfills, loss of natural resources, increased expenditure and various types of pollutions. Utilizing waste paper as an addition to concrete production could reduce environmental pollutions. This research investigates the concrete properties containing shredded waste paper using copier and cardboard as additives for the slump of fresh concrete and splitting tensile strength of hardened concrete. All specimens are subjected to water curing at 7 and 28 days for splitting tensile strength test. The results of the slump and splitting tensile strength increase at 5% and 10% addition of shredded copier and cardboard waste paper. The finding shows that concrete containing 10% addition of shredded copier and cardboard waste paper exhibits the highest slump and splitting tensile strengths. Furthermore, the results also show that shredded cardboard waste paper has higher slump and splitting tensile strength than shredded copier waste paper for all addition percentages. This study indicates that shredded copier and cardboard waste paper can be used as additional material in concrete production.